If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -1)(3x + -1) = 12 Reorder the terms: (-1 + 3x)(3x + -1) = 12 Reorder the terms: (-1 + 3x)(-1 + 3x) = 12 Multiply (-1 + 3x) * (-1 + 3x) (-1(-1 + 3x) + 3x * (-1 + 3x)) = 12 ((-1 * -1 + 3x * -1) + 3x * (-1 + 3x)) = 12 ((1 + -3x) + 3x * (-1 + 3x)) = 12 (1 + -3x + (-1 * 3x + 3x * 3x)) = 12 (1 + -3x + (-3x + 9x2)) = 12 Combine like terms: -3x + -3x = -6x (1 + -6x + 9x2) = 12 Solving 1 + -6x + 9x2 = 12 Solving for variable 'x'. Reorder the terms: 1 + -12 + -6x + 9x2 = 12 + -12 Combine like terms: 1 + -12 = -11 -11 + -6x + 9x2 = 12 + -12 Combine like terms: 12 + -12 = 0 -11 + -6x + 9x2 = 0 Begin completing the square. Divide all terms by 9 the coefficient of the squared term: Divide each side by '9'. -1.222222222 + -0.6666666667x + x2 = 0 Move the constant term to the right: Add '1.222222222' to each side of the equation. -1.222222222 + -0.6666666667x + 1.222222222 + x2 = 0 + 1.222222222 Reorder the terms: -1.222222222 + 1.222222222 + -0.6666666667x + x2 = 0 + 1.222222222 Combine like terms: -1.222222222 + 1.222222222 = 0.000000000 0.000000000 + -0.6666666667x + x2 = 0 + 1.222222222 -0.6666666667x + x2 = 0 + 1.222222222 Combine like terms: 0 + 1.222222222 = 1.222222222 -0.6666666667x + x2 = 1.222222222 The x term is -0.6666666667x. Take half its coefficient (-0.3333333334). Square it (0.1111111112) and add it to both sides. Add '0.1111111112' to each side of the equation. -0.6666666667x + 0.1111111112 + x2 = 1.222222222 + 0.1111111112 Reorder the terms: 0.1111111112 + -0.6666666667x + x2 = 1.222222222 + 0.1111111112 Combine like terms: 1.222222222 + 0.1111111112 = 1.3333333332 0.1111111112 + -0.6666666667x + x2 = 1.3333333332 Factor a perfect square on the left side: (x + -0.3333333334)(x + -0.3333333334) = 1.3333333332 Calculate the square root of the right side: 1.154700538 Break this problem into two subproblems by setting (x + -0.3333333334) equal to 1.154700538 and -1.154700538.Subproblem 1
x + -0.3333333334 = 1.154700538 Simplifying x + -0.3333333334 = 1.154700538 Reorder the terms: -0.3333333334 + x = 1.154700538 Solving -0.3333333334 + x = 1.154700538 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + x = 1.154700538 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + x = 1.154700538 + 0.3333333334 x = 1.154700538 + 0.3333333334 Combine like terms: 1.154700538 + 0.3333333334 = 1.4880338714 x = 1.4880338714 Simplifying x = 1.4880338714Subproblem 2
x + -0.3333333334 = -1.154700538 Simplifying x + -0.3333333334 = -1.154700538 Reorder the terms: -0.3333333334 + x = -1.154700538 Solving -0.3333333334 + x = -1.154700538 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + x = -1.154700538 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + x = -1.154700538 + 0.3333333334 x = -1.154700538 + 0.3333333334 Combine like terms: -1.154700538 + 0.3333333334 = -0.8213672046 x = -0.8213672046 Simplifying x = -0.8213672046Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.4880338714, -0.8213672046}
| 3x=4x-1 | | 2x=2-3x | | (4Y^3-2Y^2)+(7Y^2+3Y-y)= | | 7.4x+51.8=103.6 | | 9AB^2+8AB^2= | | 4x-17+6x-28=15 | | 6m=26 | | 9AB^2-8AB^2= | | 5(2x+3)=6(x-1)+4x | | 50(x-5)=30(x+5) | | 8+4x=9x | | 2x+5=-(2+3x) | | 3p+4=-10p-8 | | 8(2x+3)=4(4x+6) | | -12x=-9x+21 | | 3x^2-54x+241=0 | | 3(x-3)+2(2x)=5 | | 9w=-4w-52 | | 5(2z-3)=15 | | 10y=8y+12 | | 3u-15=7(u-5) | | 2(4x-7)+6=3(5x+2)+7x | | 5x(8+7)+7= | | .2x+.5(12-x)=3.6 | | 8p-6=50 | | 27=5x+3 | | -12=-s | | 3x=5x+3 | | -z=-10 | | 10x-3=8x+9 | | 2(x-4)+8=3x-3 | | 40-12+3x-14+x=18 |